Following the Film Footprints of Antarctica: A Comprehensive Project for the Rescue of Argentine Antarctic Cinema - Fontana, Pablo Gabriel; Levinson, Andrés Patricio
Antarctica has been the protagonist and setting for numerous Argentinean film productions, some of which are now unknown. This represents a vast audiovisual heritage of profound documentary value, allowing us to access various national representations of this continent. Here, we provide a brief overview of the most prominent titles in this cinematography, much of which has been preserved since 2018 through a joint project between the Argentine Antarctic Institute and the Pablo Ducrós Hicken Film Museum in the Autonomous City of Buenos Aires. We delve into the general aspects of this “Comprehensive Project for the Rescue of Argentinean Antarctic Cinema,” which involves the rescue, preservation, research, digitization, and accessibility of Argentine films made in Antarctica throughout the 20th century. Each film holds immeasurable value because the images captured in every frame constitute an essential part of Antarctic memory. The effort to preserve them, in a very basic sense, is about making them visible. Fil: Fontana, Pablo Gabriel. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Levinson, Andrés Patricio. Museo del Cine Pablo Ducrós Hicken; Argentina